Analysis of Instrument Validity and Needs for Ethno-STEM Based Science E-Modules to Strengthen Pancasila Student Profiles - Bramastia; Suciati; Febriarini Sarwendah Asri Nugraheni (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the results of the validation of the needs questionnaire and determine the needs of Ethno-STEM-based learning modules to strengthen the Pancasila student profile. This study uses the Research and Development (R&D) method with the Borg and Gall model which focuses on five stages. The results of the study showed that the validation of the needs questionnaire on content validation were 65.33% and the results of the language validation on the Pancasila student profile questionnaire instrument were 65.66% with a good category. The results of the Vindeks analysis on the content validation indicator were 0.91; 0.92; 0.91 and the Vindeks on the language validation indicator was 0.91; 0.92; 0.92 with a valid category on each indicator. The Vindeks results show that the instrument is valid in measuring the character of the Pancasila student profile. Furthermore, based on the results of the needs analysis, it was found that the understanding of junior high school students in Solo Raya regarding the sub-elements of the Pancasila Student Profile ranged from 34-67%, indicating that efforts were needed to strengthen student character. Further Ethno-STEM modules were needed to strengthen the character of the Pancasila Student Profile in all six dimensions.